Zimbabwe's Cinematic Arts : Language, Power, Identity - Thompson, Katrina Daly, 1975- (Book collections on Project MUSE., 2012)
This timely book reflects on discourses of identity that pervade local talk and texts in Zimbabwe, a nation beset by political and economic crisis. As she explores questions of culture that play out in broadly accessible local and foreign film and television, Katrina Daly Thompson shows how viewers interpret these media and how they impact everyday life, language use, and thinking about community. She offers a unique understanding of how media reflect and contribute to Zimbabwean culture, language, and ethnicity.